Failure Simulation in Software-Defined Networks with Differential Link Availability - Melo, Manuel Paulo Albuquerque (2021)
In Software-Defined Networks (SDN) the placement of controllers is an important factor for overall network reliability. Whereas most studies assume that all links have similar link failure rates/availability, placing controllers taking into account differences in link availability can yield advantages. This is even more relevant if the network is designed with a particular subset of high availability links (a spine). After presenting integer linear programming formulations to support controller placement considering differential link availability, we propose a simulation approach to verify the reliability change due to that placement. From a simulational study using 2 networks, 30 different link availability configurations we found a definite advantage in overall reliability in using the knowledge of high availability links to place the controllers. However, while there were also advantages to using certain spines for individual networks, these advantages were not uniform, and varied according to networks, the number of controllers placed and link availability ratio. Further work is suggested to check whether fault patterns may influence the reliability advantage of individual spines.